2020
DOI: 10.7203/sjp.28.2.17850
|View full text |Cite
|
Sign up to set email alerts
|

Late Jurassic-Early Cretaceous freshwater bivalves from Turiasaurus riodevensis bearing strata of Teruel (Spain)

Abstract: Three freshwater bivalve taxa are described from the Villar del Arzobispo Formation (Late Jurassic-Early Cretaceous) of Riodeva, Teruel, Spain. The stratigraphic range of the large and geographically widely distributed bivalve Margaritifera, previously recorded from the Early Cretaceous of Spain and southern England, is recognised to extend back probably into the Late Jurassic. This new record extends the palaeogeographic and temporal distribution of the family Margaritiferidae in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The present results highlight that the placement of several Jurassic and Early Cretaceous margaritiferid species within the genus Margaritifera (e.g., Delvene et al, 2013Delvene et al, , 2016Van Damme et al, 2015) needs to be revised because these taxa most likely represent ancestral fossil lineages that are not directly associated with the crown group of the latter genus despite their morphological similarity. The description of two fossil species from the same deposit on the basis of small conchological differences, a common procedure in systematic paleontology (e.g., Delvene et al, 2016), most likely leads to overestimation of the actual diversity of fossil taxa, e.g.…”
Section: Origin and Diversification Of The Margaritiferidaementioning
confidence: 89%
See 2 more Smart Citations
“…The present results highlight that the placement of several Jurassic and Early Cretaceous margaritiferid species within the genus Margaritifera (e.g., Delvene et al, 2013Delvene et al, , 2016Van Damme et al, 2015) needs to be revised because these taxa most likely represent ancestral fossil lineages that are not directly associated with the crown group of the latter genus despite their morphological similarity. The description of two fossil species from the same deposit on the basis of small conchological differences, a common procedure in systematic paleontology (e.g., Delvene et al, 2016), most likely leads to overestimation of the actual diversity of fossil taxa, e.g.…”
Section: Origin and Diversification Of The Margaritiferidaementioning
confidence: 89%
“…The Margaritiferinae MRCA had a continuous range from East Asia to the Mediterranean Region in the Late Jurassic, which was most likely facilitated by host fish dispersal within a continuous paleo-river system or along the Tethys coastal line (Hou and Li, 2017). The earliest history of this clade is well documented via fossil records from Jurassic deposits of North Africa and Europe (Delvene et al, 2013(Delvene et al, , 2016Van Damme et al, 2015). †"Margaritifera" crosthwaitei (Newton, 1909) from the Late Jurassic deposits of Egypt and †Asturianaia soudanensis (Van Damme & Bogan, 2015) comb.…”
Section: Origin and Diversification Of The Margaritiferidaementioning
confidence: 99%
See 1 more Smart Citation
“…dinosaurs would require the presence of permanent water sources and abundant vegetation; in fact, freshwater fossils of turtles (P erez-Garc ıa & Royo-Torres, 2014) and bivalves (Delvene et al, 2013) have been reported in the fluvial deposits of the studied succession in the South-Iberian Basin. Nevertheless, given the coastal setting of the studied succession, mixing of fresh and marine waters or local tidal influence is conceivable for some water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The lectotype and syntype (see below) specimens of M. valdensis correspond to the morphotype characterised by a very thick shell and ligament; the opposite for the second morphotype, to which topotype (see below) and the Spanish fossils belong. Subsequently, Delvene et al (2013) described scarce isolated valves from the Villar del Arzobispo Formation at Riodeva (Teruel, Spain). Among them, both morphotypes were recognised and described.…”
mentioning
confidence: 99%